2011
DOI: 10.1159/000322598
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Comparison of Target-Controlled Infusion of Remifentanil and Propofol with Desflurane and Fentanyl for Laryngeal Surgery

Abstract: Aims: To compare the clinical profile of target-controlled infusion (TCI) of remifentanil (REM) + propofol (PRO) with fentanyl (FEN) bolus infusion with desflurane (DES) inhalation in direct laryngoscopic surgery. Methods: Sixty patients who were scheduled to undergo laryngoscopic surgery were randomly assigned to two groups (n = 30, respectively). One group of patients received a TCI of REM + PRO anesthetic treatment, while the patients in the other group received a bolus infusion of FEN and DES inhalation tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…During the first 24 post-operative hours, the median (IQR) consumption of morphine was 27 mg (13-40) in the GA group and 27 mg (10-45) in the SA group (n.s.). The median number (IQR) of administered PCA doses was 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the GA group and 18 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the SA group (n.s.). The median (IQR) number of requested, but not administered, PCA doses was 24 (5-91) in the GA group and 15…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the first 24 post-operative hours, the median (IQR) consumption of morphine was 27 mg (13-40) in the GA group and 27 mg (10-45) in the SA group (n.s.). The median number (IQR) of administered PCA doses was 15 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the GA group and 18 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) in the SA group (n.s.). The median (IQR) number of requested, but not administered, PCA doses was 24 (5-91) in the GA group and 15…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to older studies, we chose to use TCI as the GA method as it produces rapid emergence from anaesthesia. 3,15 Despite recommendations, we did not use intrathecal morphine in the SA group, 16 and this may have influenced our results. However, intrathecal morphine produces a limited analgesic effect and has undesirable side effects especially for elderly.…”
Section: Spinal or General Anesthesia For Hip Arthroplastymentioning
confidence: 92%
“…The median (IQR) 24 h postoperative consumption of morphine was 19 mg (11-28) in the GA group and 54 mg (37-78) in the SA group (P,0.001). The median number (IQR) of administered PCA doses was 12 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) in the GA group and 30 in the SA group (P,0.001). The median (IQR) number of requested, but not administered, PCA doses was 2 (0-7) in the GA group and 9 (1-26) in the Duration of surgery (min) 44 (11) 49 (7) Operative bleeding (ml) 208 (145 -267) 218 (132 -293) SA group (P,0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Other differences compared with older studies are that we used TCI as the GA method as TCI is well tolerated with rapid and clear headed emergence. 15 Finally, all subjects received standardized opioid-sparing analgesia with cyclo-oxygenase-2 inhibitor and acetaminophen.…”
Section: Discussionmentioning
confidence: 99%
“…Hohlrieder et al 11 found that TIVA is associated with significantly less coughing and reduces hemodynamic response when compared with inhalation anesthesia in elective lumbar disc surgery during emergence from anesthesia. In addition, Wang et al 21 demonstrated more stable hemodynamics in the TCI patient group and significantly lower mean arterial pressure and faster recovery profiles compared with the fentanyl/DES patient group. Variable doses of intraoperative fentanyl administrated between groups may explain these differences in findings.…”
Section: Discussionmentioning
confidence: 97%